Method of Using radio-electronic Equipment Diagnostics Durable Systems and Devices for Localization of Defective Elements: Metode Penggunaan Sistem dan Perangkat Tahan Lama Diagnostik Radio-elektronik untuk Lokalisasi Elemen Cacat - Odinakhon Satvoldiyevna Olimova (Universitas Muhammadiyah Sidoarjo, 2022)
This article focuses on enhancing fault tolerance and reliability in electronic systems by providing recommendations for diagnosing and repairing basic semiconductor devices. The study introduces a novel method for diagnosing radio-electronic equipment using a device that localizes faulty elements. The goals of the research include improving fault localization accuracy and reducing repair time. The proposed method is based on the principles of fault isolation and utilizes advanced diagnostic techniques. Experimental results demonstrate the effectiveness of the approach, showcasing significant improvements in fault detection and repair efficiency. The implications of this research suggest that implementing the proposed method can enhance the reliability and maintainability of electronic systems, leading to reduced downtime and improved overall system performance. Highlights: Improved fault localization accuracy: The article presents a novel method for diagnosing radio-electronic equipment that focuses on accurately localizing faulty elements, leading to enhanced fault detection and diagnosis precision. Reduced repair time: The research aims to provide recommendations for repairing basic semiconductor devices, resulting in reduced repair time and improved system availability, ultimately minimizing downtime and improving overall system efficiency. Enhanced system reliability: By implementing the proposed method and incorporating advanced diagnostic techniques, the article highlights the potential for improving the reliability of electronic systems, leading to increased system performance and reduced maintenance efforts. Keywords: fault tolerance, reliability, electronic systems, diagnostics, repair.